(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The accuracy, reliability and compliance of activities in modern analytical testing laboratories directly depend on an effectively functioning quality system. The quality management system (QMS) serves not only as a means of documenting and managing results in the laboratory, but also as the main infrastructure ensuring the stability of processes. Therefore, international standards such as ISO/IEC 17025:2017 and ISO 9001:2015 impose strict requirements on the laboratory quality system. In particular, requirements such as continuous quality improvement, risk-based thinking, documented information management, internal audits and elimination of undetected nonconformities have become an integral part of laboratory activities. This article analyzes improved risk management methods in testing laboratories, their digitalization, and the process of integrating them into the quality management system.